E-220 Comparing treatment outcomes of various intracranial bifurcation aneurysms locations using woven endobridge (WEB) device. (23rd July 2022) - Adeeb, N
Abstract : Background: The Woven EndoBridge (WEB) device has FDA approval for treatment of wide-necked intracranial bifurcation aneurysms. While the WEB device has proven to result in adequate occlusion in bifurcation aneurysms overall, its utility in the individual bifurcation locations has only been evaluated separately in few case series which were limited by small sample sizes. The present study aims to compare angiographic and clinical outcomes after treatment of bifurcation aneurysms at various locations, including Acom, ACA bifurcation distal to Acom, basilar tip, ICA bifurcation, and MCA bifurcation aneurysms using the WEB device. Methods: A retrospective cohort analysis was conducted at 22 academic institutions worldwide to compare treatment outcomes of patients with intracranial bifurcation aneurysms using the WEB devices. Data includes patient and aneurysm characteristics, procedural details, angiographic and functional outcomes, and complications. Results: A total of 572 aneurysms were included. MCA (36%), Acom (35.7%), and basilar tip (18.9%) aneurysms were most common. The rate of adequate aneurysm occlusion was significantly higher for basilar tip (91.6%) and ICA bifurcation (96.6%) aneurysms and lower for ACA bifurcation (71.4%) and Acom (80.6%) aneurysms (p = 0.04). Conclusion: To our knowledge, this is the most extensive study to date that compares the treatment of different intracranial bifurcation aneurysms using the WEB device. Basilar tip and ICA bifurcation aneurysms showed significantly higher rates of aneurysms occlusion compared to other locations. These finding are crucial to guide management of bifurcation aneurysms as it shows that MCA bifurcation and Acom aneurysms might not be ideal candidates for WEB device and could benefit from other modalities of treatment, including microsurgical clipping. Further studies comparing those modalities are needed. Disclosures: N. Adeeb: None.